Self-Esteem and its Relationship to the Educational Values of Athlete Students (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study aimed to identify the degree of self-esteem and its relationship to the educational values of student athletes. The researcher used the descriptive approach. The study sample consisted of 93 players, (40) male and (53) female high school students, in Al-Karak Governorate in Jordan, who won the championships of basketball, handball, and volleyball. To achieve the goals of the study, the researcher used the Rosenberg scale for self-assessment and the educational value scale. To answer the study questions, mean and standard deviation were used, and the T-test was used to identify gender differences, and correlation coefficient was employed to identify the relationship between self-esteem and educational values ​​among  athlete students.The results of the study revealed a high degree of self-esteem in both male and female players. In terms of values, the results indicated that cognitive values ranked first, followed by aesthetic values. Social values are ranked fifth for both male and female playersEconomic values are ranked third, followed by moral values, for male players, while moral values are ranked third, followed by economic values, for female players.The results also indicated that there are statistically significant differences when it comes to aesthetic values only, in favor of female players. Also, of the findings of the study is that there was a corealtion, ranging between weak and very weak, between the value of self-esteem and that of the educational values of both men and women. Hoowever, there is a statistically significant corelation (a £ 0.05) between the value of self-esteem and the that of cognitive values of the female players. The researcher recommended the necessity of conducting studies to verify the extent to which schools provide the human and material capabilities that can be used to provide students with the necessary positive values in society, in addition to the need for teachers and trainers to enhance self-esteem among students first and win the match second
Keywords: Self-Esteem; Educational Values; Athlete Students